Mapping Escolar ( Lepidocybium flavobrunneum ) in Motion: Oceanographic Forces Shaping Its Habitat in the Southwestern South Atlantic, With Insights From Fishers' Perceptions - Lucas Rodrigues; Maria Grazia Pennino; Paul Gerhard Kinas; David Conesa; Alba Fuster‐Alonso; Andrés Domingo; Rodrigo Forselledo; Federico Mas; Bruno Mourato; Rodrigo Sant'Ana; Vinni Santos Thykjaer; Raquel Virginia Marquez Marquez; et al. (Fisheries Oceanography, 2026)
Lepidocybium flavobrunneum [Smith, 1843], commonly known as escolar, is a large pelagic species, important for global and local fisheries, particularly in the southwestern South Atlantic Ocean (SWAO), where it constitutes a significant portion of the catch. However, despite its important socioeconomic role, it remains less studied compared to other large pelagic species. Enhancing research efforts is therefore key to better understanding the ecological processes that influence its spatial and temporal distribution. To address this gap, our study applied species distribution models (SDMs) to escolar's occurrence and abundance using longline fleet data from south Brazil and Uruguay. Estimation and prediction were conducted at the Bayesian framework using the integrated nested Laplace approximation (INLA) methodology combined with the stochastic partial differential equation (SPDE) approach. Our findings reveal a strong correlation between warmer sea surface temperatures and increased escolar occurrence and abundance in the SWAO, particularly during the austral summer, in contrast to cooler‐season patterns observed elsewhere. Escolar's distribution is influenced by the southward and westward movement of seawater driven by the Brazil Current, and its preference for depths greater than 2000 m reflects its oceanic nature. Predicted areas of higher abundance around the continental slope (between 33° and 37° S) and the Rio Grande Rise are linked to the dynamic interaction of warm and cold currents and nutrient‐rich waters. Additionally, escolar's sensitivity to low‐light conditions may explain reduced catches during moonlit nights. A complementary analysis assessing the synergistic influence of sea surface temperature and lunar illumination on escolar occurrence indicated that, under high temperatures (> 22 °C), occurrence is further enhanced during dark nights. Furthermore, semi‐structured interviews with vessel captains revealed that 90% identified temperature (via open‐ended responses) as a key environmental factor driving escolar catches, and 80% of them attributed a strong influence (greater than average catch rates) to temperature, summer season and new moon phase. This study provides new insights into escolar's seasonal and spatial patterns, emphasizing the impact of oceanographic features and light conditions on its distribution. It also highlights the need for further research into the mechanisms driving escolar populations.

Spatial and Temporal Size Distribution of Swordfish ( Xiphias gladius ) in the Atlantic Ocean: Implications for Conservation and Management - Daniela Rosa; Michael Schirripa; Kyle Gillespie; David Macías; Rodrigo Forselledo; Bruno Mourato; Mikihiko Kai; Freddy Arocha; Nan-Jay Su; Sven Kerwath; Laurent Bahou; Luigi Pappalardo; et al. (Reviews in Fisheries Science & Aquaculture, 2025)

Sea turtles in the Atlantic and Indian Oceans, a step towards understanding bycatch and management of these species in tuna fisheries - Andrés Domingo; José Carlos Baéz; Philip Miller; Denham Parker; María Lourdes Ramos; Philippe S. Sabarros; Craig Brown; Juan Antonio Camiñas; Rui Coelho; Rodrigo Forselledo; Fernando Niemeyer Fiedler; Bruno Giffoni; et al. (Biological Conservation, 2025)

Interspecific variability in plastic ingested by Procellariiformes off the Uruguayan coast - Joaquín Muñoz; Rodrigo Forselledo; Andrés Domingo; Sebastián Jiménez (Marine Pollution Bulletin, 2023)

New records and range extension of the Portuguese dogfish Centroscymnus coelolepis in the south‐western Atlantic Ocean, with comments on its morphology - Federico Mas; Rodrigo Forselledo; Andrés Domingo; Oscar Pin; Pablo Troncoso; Eugenia Errico; Alejandro Marquez; Sho Tanaka; Simon Weigmann (Journal of Fish Biology, 2020)
The Portuguese dogfish Centroscymnus coelolepis is a wide‐ranging deep‐water shark and a common by‐catch component of the catches of several mid‐ to deep‐water fisheries. In the present study, two new records from the south‐western Atlantic Ocean are reported based on specimens caught by bottom‐longline fishing vessels operating in the Argentinean–Uruguayan Common Fishing Zone. Species identification based on morphology and detailed morphometrics, as well as molecular data are presented for one of the specimens. The distribution of the species over the south‐western Atlantic is discussed on the basis of the available bibliography and a thorough revision of museum collections. The records presented here expand the species' previously acknowledged distribution southwards, from around 21° S to at least 38° S, suggesting it occurs continuously along the shelf break of eastern South America. However, given the limited access to specimens of deep‐water sharks in the region, the abundance and real extent of C. coelolepis distribution in the south‐western Atlantic as well as its interaction with deep‐water fisheries remain to be fully assessed.

Effects of best practices to reduce seabird bycatch in pelagic longline fisheries on other threatened, protected and bycaught megafauna species - Sebastián Jiménez; Rodrigo Forselledo; Andrés Domingo (Biodiversity and Conservation, 2019)

Distribution patterns and population structure of the blue shark ( Prionace glauca ) in the Atlantic and Indian Oceans - Rui Coelho; Jaime Mejuto; Andrés Domingo; Kotaro Yokawa; Kwang‐Ming Liu; Enric Cortés; Evgeny V. Romanov; Charlene da Silva; Fábio Hazin; Freddy Arocha; Aldrin Masawbi Mwilima; Pascal Bach; et al. (Fish and Fisheries, 2018)
The blue shark ( Prionace glauca ) is the most frequently captured shark in pelagic oceanic fisheries, especially pelagic longlines targeting swordfish and/or tunas. As part of cooperative scientific efforts for fisheries and biological data collection, information from fishery observers, scientific projects and surveys, and from recreational fisheries from several nations in the Atlantic and Indian Oceans was compiled. Data sets included information on location, size and sex, in a total of 478,220 blue shark records collected between 1966 and 2014. Sizes ranged from 36 to 394 cm fork length. Considerable variability was observed in the size distribution by region and season in both oceans. Larger blue sharks tend to occur in equatorial and tropical regions, and smaller specimens in higher latitudes in temperate waters. Differences in sex ratios were also detected spatially and seasonally. Nursery areas in the Atlantic seem to occur in the temperate south‐east off South Africa and Namibia, in the south‐west off southern Brazil and Uruguay, and in the north‐east off the Iberian Peninsula and the Azores. Parturition may occur in the tropical north‐east off West Africa. In the Indian Ocean, nursery areas also seem to occur in temperate waters, especially in the south‐west Indian Ocean off South Africa, and in the south‐east off south‐western Australia. The distributional patterns presented in this study provide a better understanding of how blue sharks segregate by size and sex, spatially and temporally, and improve the scientific advice to help adopt more informed and efficient management and conservation measures for this cosmopolitan species.

Pan-Atlantic distribution patterns and reproductive biology of the bigeye thresher, Alopias superciliosus - Joana Fernandez-Carvalho; Rui Coelho; Jaime Mejuto; Enric Cortés; Andrés Domingo; Kotaro Yokawa; Kwang-Ming Liu; Blanca García-Cortés; Rodrigo Forselledo; Seiji Ohshimo; Ana Ramos-Cartelle; Wen-Pei Tsai; et al. (Reviews in Fish Biology and Fisheries, 2015)